Photocatalytic Conversion of CO2 into Methanol: Significant Enhancement of the Methanol Yield over Bi2S3/CdS Photocatalyst - M. Rahim, Uddin; Khan, Maksudur R.; Md. Wasikur, Rahman; Cheng, C. K.; Yousuf, Abu (Penerbit Universiti Malaysia Pahang, 2015)
The present work is a significant approach to explore the photo-conversion of carbon dioxide (CO2) into methanol on Bi2S3/Cds photocatalyst under visible light irradiation. In this perspective, Bi2S3 nanoparticles have been successfully synthesized via corresponding salt and thiourea assisted sol-gel method. An innovative hetero-system Bi2S3/CdS has been proposed to achieve methanol photo evolution and its photocatalytic activities have been investigated.